Inflammation and its associations with aortic stiffness, coronary artery disease and peripheral artery disease in different ethnic groups: The HELIUS Study. (August 2021) - Hayfron-Benjamin, Charles F.; Mosterd, Charlotte; Maitland - van der Zee, Anke H.; van Raalte, Daniel H.; Amoah, Albert G.B.; Agyemang, Charles; van den Born, Bert-Jan
Abstract: Background: evidence shows important ethnic differences in vascular dysfunction rates; however, the mechanisms driving these differences remain unclear. One potential factor is the ethnic differences in the role of inflammation in vascular injury. We tested the hypothesis that low-grade inflammation is unequally associated with vascular dysfunction in different ethnic groups. Methods: we included 5698 participants (similar-sized Dutch, African Surinamese, South-Asian Surinamese, Ghanaians, Turkish, and Moroccans) of the HELIUS study (the Netherlands) conducted between 2011 and 2015. Logistic regression was used to examine the associations of Z-score inflammatory biomarker concentration (high sensitivity C-reactive protein [hs-CRP], fibrinogen, and d -dimer) with vascular dysfunction (aortic stiffness, coronary artery disease [CAD], and peripheral artery disease [PAD]), with adjustments for age, sex, smoking (pack-years), BMI, hypertension, HbA1c, total cholesterol, and statin use Findings: in the fully adjusted models, higher Z-score hs-CRP was positively associated with CAD in Dutch [OR 1·63, (95% CI 1·21–2·18)] and PAD in South Asians [1·25(1·03–1·53)], respectively. Higher Z-score fibrinogen was positively associated with CAD in African Surinamese [1·28(1·03–1·59)] while higher Z-score d -dimer was positively associated with PAD in Moroccans [1·39(1·01–1·93)]. Higher Z-score hs-CRP [0·71(0·54–0·94)] and fibrinogen [0·75(0·58–0·97)] concentrations were negatively associated with PAD in African Surinamese. Interpretation: our study shows that inflammatory biomarkers are unequally associated with vascular dysfunction in different ethnic groups. These observations provide opportunities for future studies aimed at assessing the predictive roles of inflammation on vascular disease in different ethnic groups. Funding: The HELIUS study is also funded by research grants of the Dutch Heart Foundation (Hartstichting; Grant no. 2010T084), the Netherlands Organization for Health Research and Development (ZonMw; Grant no. 200, 500, 003), the European Integration Fund (EIF; Grant no. 2013EIF013) and the European Union (Seventh Framework Programme, FP-7; Grant no. 278, 901).